Fairy Tales as a Catalyst for Immersion into the World of Economics - Holovashchuk, Yevheniia (2019)
The aim of the thesis is to show how fairy tales shape people’s understanding of the economy and what consequences this may have. In order to investigate the effects of stories an experimental research was conducted with children of a pre-school age. Two hypotheses were tested: firstly, that fairy tales can directly improve the rate of economic awareness among kids and secondly, that they lead to a decrease in the achievement gap. The experiment consisted of two questionnaires in the form of games and a story. According to the obtained results, the level of economic awareness among children increased due to the introduction of a story, however, in case of the achievement gap no changes were observed.